The use of video technologies in refereeing football and other sports - Armenteros, Manuel; Benítez, Anto J.; Betancor, Miguel Angel (Routledge research in sports technology and engineering, 2020)
For a long time, various different lobbying sectors have claimed that the use of video technology is an effective aid in decision-making. Now the IFAB has taken a historic step in the approval of experiments on the use of video to provide support to football refereeing. The Use of Video Technologies in Refereeing Football and Other Sports analyses the capacity of audio-visual technology from different perspectives to help understand the best implementation of the Video Assistant Referee (VAR) system in football and, more generally, in other sports. This book addresses in-depth interdisciplinary viewpoints on the need and the opportunity of the implementation procedures regarding how to use it, considering that it could lead to very important changes. The book goes on to examine various approaches to the most interesting topics for players, amateurs, coaches, referees and referees coaches. Offering viewpoints from both academics and professionals, this new volume addresses the VAR issue in a multidisciplinary way, analysing the implications of video replay application in football from the perspective of players, coaches, television professionals, referees, amateurs, sports lawyers, media and educators.